AB0102 Impairment of granzyme b-producing regulatory b cells exacerbated rheumatoid arthritis. (15th June 2017) - Xu, L; Hu, F; Liu, X; Zhu, L; Ren, L; Liu, H; Zhu, H; Su, Y
Abstract : Background: Rheumatoid arthritis (RA) is a common and complex autoimmune disease characterized by chronic inflammation and cartilage/bone damage involving numerous cells, such as T cells, B cells, chondrocytes, fibroblasts [1] . B cells had long been well-demonstrated to participant in the development of RA [2] . Except producing specific antibody and inducing T cell activation, impaired immunosuppressive function of B cells further emphasized their roles in RA recently [3] . Objectives: To investigate whether B cells could produce granzyme B and the potential role in the pathogenesis of Rheumatoid arthritis (RA). Methods: To reveal the expression of granzyme B in B cells, flow cytometry, PCR and Elispot were performed. The role of IL-21 and anti-BCR stimulation on granzyme B expression was assessed by in vitro stimulation assay. CD4 + T cell-B cell co-culture in the presence of granzyme B neutralizing antibody was performed to demonstrate the function of these cells. Then the levels of granzyme B in B cells between RA patients, OA patients as well as HCs were compared. Next, the correlation analysis between granzyme B-producing B cells and clinical features in RA patients was performed. Finally, the frequencies of granzyme B-producing B cells in RA patients before and after therapy were also evaluated using flow cytometry. Results: B cells could spontaneously produce granzyme B, which could be perpetuated by IL-21 and anti-BCR stimulation. The frequencies of Th1 and Th17 cells were significantly elevated under the condition of granzyme B blockade when granzyme B was neutralized in CD4 + T cell-B cell co-culture. In RA patients, but not OA patients and HCs, the frequencies of granzyme-B producing Bregs decreased significantly, which was functionally impaired and negatively correlated with disease activity score 28. Moreover, after effective clinical therapy, the frequencies could recover to nomal levels. Conclusions: B cells could exert the regulatory functions via granzyme B production. Under RA circumstance, these granzyme B-producing Bregs were impaired and contributed to the disease progression. References: Smolen JS, Aletaha D, McInnes IB, Rheumatoid arthritis, Lancet. 2016 Oct 22;388(10055):2023–2038. doi: 10.1016/S0140–6736(16)30173–8. Nakken B, Munthe LA, Konttinen YT, et al, B-cells and their targeting in rheumatoid arthritis–current concepts and future perspectives. Autoimmun Rev. 2011 Nov;11(1):28–34. doi: 10.1016/j.autrev.2011.06.010. Daien CI, Gailhac S, Mura T, Regulatory B10 cells are decreased in patients with rheumatoid arthritis and are inversely correlated with disease activity. Arthritis Rheumatol. 2014 Aug;66(8):2037–46. doi: 10.1002/art.38666. Acknowledgements: This study was supported by grants from the Natural Science Foundation of China (81671609, 81671604, 31470039). Disclosure of Interest: None declared